Correlations between the 1960 entrance requirements and academic achievements of the sophomore students of the U.P. High School - Porter, Josefina Yap 1924- (s.n.], 1965)
This study determines the existing relationships between the different indices in the entrance requirements. It also explores academic achievements at the UP High School.